The effect of a minor constituent of essential oil from Citrus aurantium: The role of beta-myrcene in preventing peptic ulcer disease - Bonamin, Flavia [UNESP]; Moraes, Thiago M. [UNESP]; Santos, Raquel C. dos [UNESP]; Kushima, Hello [UNESP]; Faria, Felipe M.; Silva, Marcos A. [UNESP]; Junior, Ivan V. [UNESP]; Nogueira, Leonardo [UNESP]; Bauab, Taís Maria [UNESP]; Souza Brito, Alba R. M.; Rocha, Lucia R. M. da [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Elsevier B.V., 2014)
The monoterpene beta-myrcene has been widely used in cosmetics, food and beverages, and it is normally found in essential oil from citrus fruit. The aim of this study was to investigate the anti-ulcer effects of beta-myrcene on experimental models of ulcers that are induced by ethanol, NSAIDs (non-steroidal anti-inflammatory drugs), stress, Helicobacter pylori, ischaemia-reperfusion injury (I/R) and cysteamine in order to compare with the essential oil of Citrus aurantium and its major compound limonene. The results indicate that the oral administration of beta-myrcene at a dose of 7.50 mg/kg has important anti-ulcer activity with significantly decreased gastric and duodenal lesions as well as increased gastric mucus production. The results showed treatment with beta-myrcene caused a significant increase in mucosal malondialdehyde level (MDA), an important index of oxidative tissue damage. The beta-myrcene was also endowed with marked enhancement of antioxidant enzyme activity from GR system as evidenced by the decreased activity of superoxide dismutase (SOD) and increased levels of glutathione peroxidase (GPx), glutathione reductase (GR), and total glutathione in gastric tissue. Our results also shown that treatment with beta-myrcene is not involved with thioredoxin reductase (TrxR) activity. Our results reveal, for the first time, the importance of beta-myrcene as an inhibitor of gastric and duodenal ulcers and demonstrate that an increase in the levels of gastric mucosa defence factors is involved in the anti-ulcer activity of beta-myrcene. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: beta-Myrcene; Peptic ulcer; Helicobacter pylori; Gastroprotection; Antioxidant effects